The Dyirbal language of north Queensland - Dixon, R. M. W. (Cambridge studies in linguistics ;, 1972)
Revision of sections on grammar & phonology of authors Ph.D. Thesis; brief introduction to grammatical characteristics of Australian languages (including map); Dyirbal; Linguistic type, dialects (Dyirbal, Giramay, Mamu, Gulngay, Dyiru, Ngadyan) & tribes speaking them (including map), surrounding languages, culture and contact history; detailed discussion of grammatical facts of Dyirbal - word classes, syntax, phonology; discussion of deep syntax in terms of transformational grammar nominative - ergative deep structure, possessive phrases as a type of relative clause, relation between nominal and verbal instrumental constructions; phonology; semantics including data on mother-in-law avoidance language; structure of lexical roots; onomatopoeia; prehistory; general discussion of lexical diffusion in Australia & inapplicability of lexicostatistic methods; evolution of the Dyirbal dialects, recent augmentation of mother-in-law vocabulary; language movement in the Cairns rain forest region; reconstruction of grammatical changes in Dyirbal; Dyirbal logic; previous work on the language; three texts, one with morpheme-by-morpheme glosses & all with literal running translations - the first man, the first baby and the origin of female sexual organs (Mamu dialects); autobiographical story involving dambun, a legendary spirit (Dyirbal dialect); story of Mubunginmi, who became a rainbow serpent (Mamu); vocabulary, limited to items occurring in grammatical examples & texts; index of affixes; includes many references throughout to other Australian languages (indexed); original analysis of demonstrative pronouns in Wemba-Wemba.